PENERAPAN FUNGSI MANAJEMEN PEMERINTAHAN DESA TEBING LINGGAHARA BARU DALAM MENYEJAHTERAKAN BILAL MAYIT - Tanjung, Habibullah; Ritonga, Hasnun Jauhari (Academy of Education Journal, 2023)
The obligation that must be carried out by Muslims towards the bodies of Muslims is an obligation that is punished by fardhu kifayah, so people who are experts and understand the procedures for carrying out fardhu kifayah worship are needed. The purpose of this study was to determine the government management of Tebing Linggahara Baru Village, West Bilah District, Labuhanbatu Regency in the welfare of the deceased. The profession of the Bilal Mayit is very noble, so the village government is expected to carry out the function of village government management and provide welfare to the Bilal Mayit. The method used is qualitative descriptive approach. Data collection from field observations and interviews. The results of the study show that the village government has carried out management functions even though it has not been maximized for the welfare of the deceased. The number of dead bodies is only 14 people for 10 hamlets due to the lack of a village government budget. With a salary of Rp. 400,000 / month, of course it cannot bring prosperity to the deceased. However, with this noble work Bilal Miyat does not pursue material things but seeks the pleasure of Allah SWT and also as a provision for the hereafter.